(untitled) (Journal of Bio-Science, 2014)
Context: Repellency test can play an important role in special environmental conditions. Objectives: The main objective of this study was to make a standard protocol to control the pest by screening the test materials using adult beetles by repellency test to see whether or not the extracts contain any potential to repel the stored grain pest. Materials and Methods: The experiment was conducted in choice chamber, which was divided by half filter paper discs (Whatman No. 40, diameter 9 cm). One half of the filter paper was loaded with untreated (control) and the other half was loaded with the extract of A. augusta. All the CHCl3 extracts were separately applied onto each of the half-discs and allowed to dry out in the air for 10 mins. Each treated half-disc was then attached lengthwise, edge-to-edge, to a control half-disc with adhesive tape and placed in petri dishes. The orientation of the same was changed in the replicates to avoid the effects of any external directional stimulus affecting the distribution of the test insects Tribolium castaneum (Herbst). Ten adult insects were released in the middle of each of the filter-paper circles and each test was replicated five times. Results: All the test extracts of seed, leaves, root wood, stem bark and stem wood of A. augusta collected in chloroform showed repellent activity against adult beetles of T. castaneum at dose levels of 314.540, 157.270, 78.635, 39.318, 19.659 and, 9.831 ?g/cm2 on filter paper. According to the intensity of repellency the results could be arranged in the order: stem bark >seed> root wood > leaf > stem wood and in all the cases significant differences were obtained. Conclusion: The present results revealed that A. augusta extracts can be used as a reduced risk repellent compound in the grain and cereal stores to manage the population of T. castaneum. The results also seen to be encouraging when there is a greater need for environment-friendly pesticides then ever before. DOI: http://dx.doi.org/10.3329/jbs.v20i0.17655 J. bio-sci. 20: 49-55, 2012